Dysfunctional endometres in Libreville: 20 years retrospective study - Barthélemy, Mabika; Ghislain, Mbadinga N.; Solange, Nguizi O. Sidonie; Grégoire, Mendome (International Journal of Research in Medical Sciences, 2021)
Background: The objectives of this work were to inventory the different morphological entities, to alert the medical class to the need for multidisciplinary care; to sensitize the health authorities on this pathology having a considerable influence on the fertility of the woman and a possible evolution towards cancerous disease. Methods: A retrospective study was carried out over 20 years from January 1983 to December 2002 at the laboratory of anatomy pathology of the faculty of health sciences in Libreville. The revealing clinical signs were the couple’s bleeding and infertility. Curettage, endometrial biopsy, and subtotal or total hysterectomy were fixed with 10% buffered formalin or Bouin’s fluid. After staining, histological study was carried out by the pathologist. Results: The histological images of the endometrial polyps were the most representative (73 cases or 17.68%), followed by prolonged proliferative endometers (70 cases, or 16.95%), glandulo-cystic hyperplasia (66 cases, or 15.98%) and persistent proliferative endometers (58 cases, or 14.04%). More than half of the numbers concerned women under 35 (225/413 cases); in those over 45 years of age, the predominantly endometrial carcinoma was found. The most affected province was Woleu-Ntem (24%), followed by Haut-Ogooué (18%). Conclusions: The different dysfunctional endometers are also described in the different regions of the continent. The management of these aims to be multidisciplinary and urgently requires a frank collaboration between clinician and morphologist, especially for country where a birth policy is clearly expressed by governing bodies.